Seed and Seedling Biology of the Woody-fruited Proteaceae - Lamont, Byron; Groom, Philip (1998)
Within the Proteaceae, 353 species confined to 7 genera in the Grevilleoideae have woody fruits. The majority (> 70%) occur in fire-prone vegetation on nutrient-poor, summer-dry soils of south-western Australia. These species are characterised by large, winged seeds contained within serotinous follicles. Seed release is mediated by desiccation of the follicle walls resulting from fruit death, although wet–dry cycles are required in some genera. After release, germination must take place by the next wet season, as the seeds are not long-lived. Seeds are particularly high in protein (40–60%), P (1–2%) and Fe (10–60‰) compared with other Proteaceae. Seeds are favoured food for pre- and post-dispersal granivores (insects, birds, rodents) and young seedlings are favoured by herbivores (insects, marsupials), with the more serotinous fruits providing extra protection for their seeds. Successful establishment is facilitated by the protective and water retentive role of the testa during germination, and the remobilisation of N and P from the cotyledons to the seedling within 10 weeks of emergence. Drought stress reduces seedling establishment in otherwise favourable postfire microsites and prevents it (assisted by herbivores) in mature vegetation. Typically, < 10% of seeds released after fire become seedlings, and < 50% of these survive the first summer. Among fire-killed species, species that produce few seeds are more likely to have drought-resistant seedlings, often associated with larger seeds and/or needle-shaped leaves. Species that resprout after fire produce a few large viable seeds per plant, whereas fire-killed species produce many smaller seeds. Of all the Proteaceae, the ecology of woody-fruited species is best known, providing great scope for comparative biology studies.